Communication and Capitalism A Critical Theory - Fuchs, Christian (University of Westminster Press, 2020)
'An authoritative analysis of the role of communication in contemporary capitalism and an important contribution to debates about the forms of domination and potentials for liberation in today's capitalist society.' - Professor Michael Hardt, Duke University, co-author of the tetralogy Empire, Commonwealth, Multitude, and Assembly 'A comprehensive approach to understanding and transcending the deepening crisis of communicative capitalism. It is a major work of synthesis and essential reading for anyone wanting to know what critical analysis is and why we need it now more than ever.' - Professor Graham Murdock, Emeritus Professor, University of Loughborough and co-editor of The Handbook of Political Economy of Communications Communication and Capitalism outlines foundations of a critical theory of communication. Going beyond Jürgen Habermas' theory of communicative action, Christian Fuchs outlines a communicative materialism that is a critical, dialectical, humanist approach to theorising communication in society and in capitalism. The book renews Marxist Humanism as a critical theory perspective on communication and society. The author theorises communication and society by engaging with the dialectic, materialism, society, work, labour, technology, the means of communication as means of production, capitalism, class, the public sphere, alienation, ideology, nationalism, racism, authoritarianism, fascism, patriarchy, globalisation, the new imperialism, the commons, love, death, metaphysics, religion, critique, social and class struggles, praxis, and socialism. Fuchs renews the engagement with the questions of what it means to be a human and a humanist today and what dangers humanity faces today.